Psychosocial Therapy Intervention Using Group Work for Women Experiencing Domestic Violence in Indonesia - Meiti Subardhini (Asian Social Work Journal, 2017)
Issues of Violence are increasing in some recent years, especially in Indonesia, including domestic violence. Victims of this violence will experience psychosocial problems ranging from mild to severe. Therefore, the Social Work profession is relevant to this issue. Previous research had been done to study the practice of Social group work through psychosocial therapy for women experiencing domestic violence, especially at the city of Bandung in West Java, Indonesia. Six (6) study subjects were used as target research through purposive technique. This study used a qualitative approach with action research methods through twelve (12) sessions by using a psychosocial therapy intervention group. Psychosocial problems experienced by members of the group (research subjects) were as follows: behavioral conditions of anxiety, stress and trauma as a result of the violence they experienced resolved through various stages in Social Work with Groups through psychosocial therapy intervention, so the practice of various techniques / psychosocial therapy as part of this study were revealed and described. The results showed that psychosocial therapy interventions group is effective to overcome the domestic violence problem.